Is agriculture an important componenet of rural tourism? - Aliza Fleischer; Anat Tchetchik (European Regional Science Association (ERSA), 2002)
In many regions rural tourism is accepted usually as a natural part of the socio-economic fabric juxtaposed with agriculture. It is clear that rural tourism is based on rural amenities, however, it is not clear how it relates to agriculture. Is agricultural activity an important and even a necessary component of rural tourism or does rural tourism provide the farmer with an auxiliary funding to continue farming? Do active farms with rural tourism enjoy economies to scope and run both businesses more efficiently than farms with only a single activity? These issues have not been approached rigorously. The objective of this paper is to investigate whether rural tourism enterprises combined with active farming differ from those without agricultural activity and how the agricultural activity affects the enterprise. The analysis is based on a face-to-face survey of 200 operators of B&B enterprises in Israel. The owners were asked about the characteristics of the B&B, labor and capital input, revenues and number of bed nights. In those cases when they were running an active farm they were asked in what manner the tourists are exposed to the agricultural amenities (i.e., is the tourist offered an activity related to the farm, how is he exposed to the agricultural landscape, etc.). About 40% had an active farm, which allowed us to compare between the two types of rural tourism businesses - with and without agricultural activity. Based on the analysis of the aforementioned data, a production function of the B&B businesses is estimated. Production is measured alternatively, by revenue or by number of bed nights, while the explanatory variables are the business characteristics, capital and labor inputs, and the agriculture characteristics for the relevant business. This analysis enables us to assess the importance of agricultural activity in the production of rural tourism services. Its results have implications on issues such as externalities between agriculture and rural tourism, between farms located at the same settlement, and the impact of governmental subsidies to agriculture may have on the development of tourism.
Keywords: 330